Improving Access and Quality in Early Childhood Development Programs : Experimental Evidence from The Gambia - Blimpo, Moussa P.; Carneiro, Pedro; Jervis, Pamela; Pugatch, Todd (World Bank, Washington, DC, 2019)
Early childhood experiences lay the foundation for outcomes later in life. Policy makers in developing countries face a dual challenge of promoting access to and quality of early childhood development services, but evidence on how to manage this trade-off is scarce. This paper studies two experiments of early childhood development programs in The Gambia: one increasing access to services, and another improving service quality. In the first experiment, new community-based early childhood development centers were introduced to randomly chosen villages that had no preexisting, structured early childhood development services. In the second experiment, a randomly assigned subset of existing early childhood development centers received intensive provider training. The analysis finds no evidence that either intervention improved average levels of child development. Exploratory analysis suggests that the first experiment, which increased access to relatively low-quality early childhood development services, led to declines in child development among children from less disadvantaged households. The evidence supports that these households may have been steered away from better quality early childhood settings in their homes. Comparisons of observationally similar children across experiments reveal that existing early childhood development centers increased language skills by 0.4 standard deviation relative to the community-based alternative, reflecting differences in program quality.